Marcas da oralidade na poesia de Manuel Bandeira - Negreiros, Gil Roberto Costa (2008)
The objective presented in this work is to analyze the marks of the orality in Manuel Bandeira s poetry. As this work establishes relations between speaking and writing, the perspective is based initially on the social interactionist perspective, that considers speaking and writing not as dichotomist positions, but as varieties that belong to the same continuum. Thus, the approach given to the research is tied to the adoption of the estimated ones of the Pragmatic, using as basic theory the analyses of the oral marks as well as the aspects of the Conversation Analysis. The analysis methodology refers to the selection of poetical stretches of the Bandeira s work that will be analyzed to the light of the chosen theory, underlain by a typological-linguistic classification and based on the lexical, syntactic and discursive levels. Throughout the analysis, many poetical stretches are compared to the excerpts of oral texts transcriptions, making possible a clearer view of the oral phenomenon present in the poems. Five chapters are presented in this study. The first one highlights Bandeira s life and his work. It also presents a reference to the presence of the spoken language in Brazilian literature, mainly to the modern phase. In the second one, a debate is proposed about the social interacionist trend, besides a thematic review concerning to the possible influence of the oral language in the literary language. In the third one, the lexical oral marks are analyzed in the corpus. In the fourth chapter, the syntactic marks are the focus of the investigation. In the fifth and last one, the discursive marks of the Manuel Bandeira s work are brought out